Effect of P. corylifolia on the pharmacokinetic profile of tofacitinib and the underlying mechanism - Wang, Yu; Zhou, Quan; Wang, Huihui; Song, Wei; Wang, Jianfeng; Mamun, Abdullah Al; Geng, Peiwu; Zhou, Yunfang; Wang, Shuanghu (Frontiers in Pharmacology, 2024)
This work aimed to explore the mechanisms underlying the interaction of the active furanocoumarins in P. corylifolia on tofacitinib both in vivo and in vitro. The concentration of tofacitinib and its metabolite M8 was determined using UPLC-MS/MS. The peak area ratio of M8 to tofacitinib was calculated to compare the inhibitory ability of furanocoumarin contained in the traditional Chinese medicine P. corylifolia in rat liver microsomes (RLMs), human liver microsomes (HLMs) and recombinant human CYP3A4 (rCYP3A4). We found that bergapten and isopsoralen exhibited more significant inhibitory activity in RLMs than other furanocoumarins. Bergapten and isopsoralen were selected to investigate tofacitinib drug interactions in vitro and in vivo. Thirty rats were randomly allocated into 5 groups (n = 6): control (0.5% CMC-Na), low-dose bergapten (20 mg/kg), high-dose bergapten (50 mg/kg), low-dose isopsoralen (20 mg/kg) and ketoconazole. 10 mg/kg of tofacitinib was orally intervented to each rat and the concentration level of tofacitinib in the rats were determined by UPLC-MS/MS. More imporrantly, the results showed that bergapten and isopsoralen significantly inhibited the metabolism of tofacitinib metabolism. The AUC(0-t), AUC(0-∞), MRT(0-t), MRT(0-∞) and Cmax of tofacitinib increased in varying degrees compared with the control group (all p < 0.05), but CLz/F decreased in varying degrees (p < 0.05) in the different dose bergapten group and isopsoralen group. Bergapten, isopsoralen and tofacitinib exhibit similar binding capacities with CYP3A4 by AutoDock 4.2 software, confirming that they compete for tofacitinib metabolism. P. corylifolia may considerably impact the metabolism of tofacitinib, which can provide essential information for the accurate therapeutic application of tofacitinib.